2013
DOI: 10.1080/17458080.2012.752582
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of capped gold nanoparticles by using various amino acids

Abstract: The production of gold nanoparticles (GNPs) by amino acid is one of the most attractive and interesting subjects in nanobiotechnology. In this study, amino acids have been utilised as a reducing agent and also an agent for capping GNPs. The GNPs were prepared using a reduction solution containing gold cations with optimum concentration of gold salt (5 mM), and also functionalised by glutamic acid, phenylalanine and tryptophan with optimum concentration of amino acids (25 mM). The optimum condition of gold solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…It has been shown that most amino acids have no interfering effects on the analysis of Xan, but compounds in the thiol-containing group, e.g., L-Cysteine, L-Glutathione, and sodium thiosulfate, which have stronger affinity to AgP [ 30 ], slightly interfere in the analysis of Xan. Zare et al have reported that L-phenylalanine can act as a reducing agent to cap gold nanoparticles [ 31 ]. In the present method, L-phenylalanine and L-alanine produced slight interference in the determination of Xan.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that most amino acids have no interfering effects on the analysis of Xan, but compounds in the thiol-containing group, e.g., L-Cysteine, L-Glutathione, and sodium thiosulfate, which have stronger affinity to AgP [ 30 ], slightly interfere in the analysis of Xan. Zare et al have reported that L-phenylalanine can act as a reducing agent to cap gold nanoparticles [ 31 ]. In the present method, L-phenylalanine and L-alanine produced slight interference in the determination of Xan.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the point of zero charge (pzc) of malachite is around pH 7.6, and malachite also has a high positive charge, ~ 20 mV on the surface at a neutral pH (Saha and Das 2009). Therefore, it can be concluded that the negatively charged amine group side chain of glutamic acid showed a high affinity for binding to positive mineral surfaces (Wang et al 2015; Wolthers et al 2008; Zare et al 2013). Whether particles stay dispersed or aggregated in a system is controlled by repulsive and attractive forces between particles, for example, gravity, electrical charge and van der Waals forces (Adamczyk and Weroński 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles have also been conjugated with peptide/ amino acid in order to produce effective and targeted delivery systems. Synthesis of AuNPs conjugated with aspartic acid, 14 glutamic acid, phenylalanine and tryptophan, 202 L-cysteine, 203 lysine, 204 and peptides 15,205 has been reported. Amino acids and peptides bind with negatively charged AuNPs through amine groups, whereas the negatively charged carboxylic groups extend outwards to stabilize AuNPs.…”
Section: Peptides and Amino Acid Conjugationmentioning
confidence: 99%